Human Resource Management (HRM) Practices and Knowledge Sharing (KS): A Case of Orange Telecommunication Company in Jordan - Al-Ghuweiri, Mohammad Awad Mousa (2011)
Previous studies have documented the impact of HRM practices on knowledge management. Also, it has been found that HRM practices play a significant role in knowledge management However, it is argued in this thesis that very limited number of studies have been conducted on the relationship between HRM practices and knowledge management especially in knowledge sharing in the perspective of developing countries in general, so this study aimed at investigating whether HRM practice have a positive impact on knowledge sharing in one of telecommunication company called Orange located in Jordan. To this end, 86 respondents working in orange telecommunication company located in Jordan were selected to participate in the study. Knowledge sharing was measured by the 7-item developed by Hsu (2008). HRM practices was measured by the 19-items This instrument have 7 items to measure training & development, 7 items to measure performance appraisal and 5 items to measure the compensation. The instrument for HRM practices was measured by using the 5-item questionnaire developed by (Singh, 2004 & Qureshi M Tahir, 2006). The findings revealed that HRM practices were statistically and significantly related to overall knowledge management. Training & development was found to be the best predictor of knowledge sharing. The limitations of this study and the recommendations for future research are also discussed.